Analisis Semiotika pada Lirik Lagu O Tano Batak Karya Siddik Sitompul - Elsa Ria Saragih; Junifer Siregar; Vita Riahni Saragih (Departement of Mathematics Education, 2023)
This research thesis is a study that aims to describe semiotics and describe icons, indexes and symbols in the lyrics of the song